Efeito de 12 semanas de treinamento isométrico de preensão manual na pressão arterial e modulação cardíaca autonômica de pacientes com doenças arterial periférica - ensaio clínico randomizado controlado - Peixoto, Roger André Oliveira (2020)
Experimental studies, systematic reviews and meta-analysis have demonstrated that isometric handgrip training (IHT) promotes reductions in blood pressure (BP) and improvement in cardiac autonomic modulation however, the effect of this modality of training in patients with peripheral artery disease (PAD), is unknown. Previous study with 4 unilateral series performed 3 times per week did not observe alterations in BP and cardiac autonomic modulation, however it is possible a training with greater volume and time could promote changes in cardiovascular parameters of these patients. Aim: Analyze the effects of IHT on BP and heart rate variability (HRV) in PAD hypertensive patients. Methods: 42 patients randomized into 2 groups were included; HIT and control group (CG). The IHT group performed 12 weeks of IHT in three weekly sessions with 8 series alternated bilaterally at 30% of maximum contraction voluntary (MVC). The CG group received a foam ball for manual compression exercise and were instructed to perform 3 sets of 10 compression. Before and after the 12 weeks of intervention was collected the systolic and diastolic brachial BP, central systolic and diastolic BP, HRV on time domain (SDNN and RMSSD) and frequency domain (Low frequency – LF, High frequency – HF and relation LF/HF. Results: After 12 weeks of IHT, no significant changes were observed in systolic brachial BP (p=0.304), diastolic brachial BP (p=0.303), central systolic BP (p=0.482), diastolic central BP (p=0.693) and HRV (p>0.05) in groups studied. Conclusion: 12 weeks of HIT with greater volume and training time not promoted alterations in cardiovascular parameters in patients with PAD.